2019
DOI: 10.3390/app9081534
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nanoparticles on Algae: Adsorption, Distribution, Ecotoxicity and Fate

Abstract: With the rapid development of nanotechnology and widespread use of nanoproducts, the ecotoxicity of nanoparticles (NPs) and their potential hazards to the environment have aroused great concern. Nanoparticles have increasingly been released into aquatic environments through various means, accumulating in aquatic organisms through food chains and leading to toxic effects on aquatic organisms. Nanoparticles are mainly classified into nano-metal, nano-oxide, carbon nanomaterials and quantum dots according to thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
67
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(79 citation statements)
references
References 102 publications
1
67
0
4
Order By: Relevance
“…In addition, AgNPs toxicity may depend on the species and on the type of growth medium in which the organisms are cultivated [44]. However, some adverse effects can also be attributed to speci c properties of NPs, such as the size and the degree of aggregation, that in seawater is increased when compared to freshwater [45,46], and that in turn affect the capacity of NPs to cross biological membrane or to bind the cell surface [47,48]. Cell wall, in fact, constitutes a primary site for interaction and serves as a barrier for the entrance of AgNPs into algal cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, AgNPs toxicity may depend on the species and on the type of growth medium in which the organisms are cultivated [44]. However, some adverse effects can also be attributed to speci c properties of NPs, such as the size and the degree of aggregation, that in seawater is increased when compared to freshwater [45,46], and that in turn affect the capacity of NPs to cross biological membrane or to bind the cell surface [47,48]. Cell wall, in fact, constitutes a primary site for interaction and serves as a barrier for the entrance of AgNPs into algal cells.…”
Section: Discussionmentioning
confidence: 99%
“…The continuous internalisation of AgNPs-G particles observed in our experiments could be dependent on the size and dispersion of our nanoparticle preparation. Data in literature report that bio-adsorption of heavy metal particles to algae is dependent on different properties of NPs, such as surface charge or size, chemical composition, and by the cell walls pore sizes, spanning through the thickness of the walls, ranging from 5 to 20 nm [47,49]. Thus, small nanostructures are highly diffusible, and only NPs up to 20 nm can reach cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Photosynthesis is an important physiological process of algal survival in the aquatic environment [34]. Previous studies [13,34] have mentioned that the adsorption of NPs on the algal surface may result in a shading effect that affects algal photosynthesis.…”
Section: Hrt and Zno Nps Effect On Algal Growthmentioning
confidence: 99%
“…Nevertheless, the presence of NPs may have an effect on photosynthetic activities because of reactive oxygen species (ROS) production. Wang et al [34] reported that in the presence of graphene oxide NPs the photosynthetic rate of algae was changed, resulting in a metabolic disturbance. Similar results were observed in the present study in the case of low HRT (20 d) where the algae were affected by the presence of ZnO NPs and the chl-a peak concentration was on the 18th day of the exposure time, whereas in the control, it was observed six days earlier.…”
Section: Hrt and Zno Nps Effect On Algal Growthmentioning
confidence: 99%
See 1 more Smart Citation